Research on work methods for tugs in ports - Paulauskas, Vytautas; Paulauskas, Donatas (Transport, 2011)
Tug assistance in ports for increasing ship maneuverability, mooring and unmooring operations is a very important issue. New tugs are given increased possibilities; nevertheless, at the same time, work methods for tugs, including advantages and disadvantages must be carefully studied, evaluated and practically applied.The article presents the results of the carried out research on the work methods of a new type of tugs, thus offering recommendations for how to avoid drawbacks of working with new tugs during ship mooring operations.First Published Online: 05 Oct 2011